SURVEI CEPAT: STRATA PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SERTA FUNGSI FISIOLOGIS KELUARGA DI DESA TAMBAKSARI KIDUL KECAMATAN KEMBARAN MEI â JUNI 2010 - Wibowo, Yudhi (MANDALA of Health, 2010)
In order to improve the Healthy and Clean Life Behavior (PHBS), the Community Health Center(Puskesmas) I Kembaran, Kembaran Sub-District, Banyumas District has tried to apply the healthpromotion strategy. But the survey of PHBS on community have not done yet by Puskesmas I Kembaran,specifically for Tambaksari Kidul village. The purpose of this rapid survey study is to know the level ofPHBS and APGAR family in the households in Tambaksari Kidul, Kembaran Sub-District, BanyumasDistrict. The population of this study is all of the 3.960 people lived in Tambaksari Kidul, Kembaran Sub-District, Kembaran District. Through the simple random sampling on the second staged, 210 heads ofhouseholds of each cluster/village were selected to be the samples for this study. The data were analyzed bystatistics descriptive. This study showed that the level of PHBS in Tambaksari Kidul, Kembaran Subdistrictwere Pratama (0,50%), Madya (21,80%), Utama (73,70%), Paripurna (3,60%) respectively. Thetarget of PHBS by 2010 was achieved beyond 65%. The value of APGAR family were the healthy family(82,25%), enough healthy family (13,82%) and unhealthy family (0,92%) respectively. The policymakers are suggested to guarantee and to keep the availability and continuity of population-based surveyfor the availability data of PHBS and APGAR family. Puskesmas must be able to manage the potential ofcommunity and the available word business in its work area and to analyze the situation as the basic of thePHBS health strategy program planning and development. Puskesmas should improve the quality of intersectoralcooperation between the unit of government organization and that of community organization.